THE INFLUENCE OF STORE ATMOSPHERE ON REVISIT INTENTION AT SHOPPING TOURISM - Dwi Febrianty Nabila; Budi Setiawan; Fitria Dina Riana (Socio-Economics/Agribusiness Department, 2021)
The tourism sector in Indonesia is growing rapidly, so the level of competition is getting higher. Shopping tourism is as one of the industries that is able to attract tourists must innovate considering the products that are sold are the same and the storeping behavior of tourists is different. This study used SEM-PLS analysis and was conducted on 110 respondents who visited Shopping Tourism in Batu city. The results showed that a well-designed store atmosphere can stimulate positive emotions of tourists, provide comfort when shopping so as to create a memorable experience, and make tourists intend to visit again in the future. This study, not only provides recommendations for creating the right store atmosphere for retailers, but also provides information on understanding the storeping behavior of tourists.